Cloud Security in Crypt Database Server Using Fine Grained Access Control - Krishna Keerthi Chennam; M. Akka Lakshmi (Institute of Advanced Engineering and Science, 2016)
Information sharing in the cloud, powered by good patterns in cloud technology, is rising as a guaranteeing procedure for permitting users to advantageously access information. However, the growing number of enterprises and customers who stores their information in cloud servers is progressively challenging users’ privacy and the security of information. This paper concentrates on providing a dependable and secure cloud information sharing services that permits users dynamic access to their information. In order to achieve this, propose an effective, adaptable and flexible privacy preserving information policy with semantic security, by using Cipher text Policy Element Based Encryption (CP-EBE) consolidated with Character Based Encryption (CBE) systems. To ensure strong information sharing security, the policy succeeds in protecting the privacy of cloud users and supports efficient and secure dynamic operations, but not constrained to, file creation, user revocation. Security analysis demonstrates that the proposed policy is secure under the generic bi- linear group model in the random oracle model and enforces fine-grained access control, full collusion resistance and retrogressive secrecy. Furthermore, performance analysis and experimental results demonstrate that the overheads are as light as possible.